Effect of Changes in Sowing Dates on Disease Severity of Roselle (Hibiscus sabdariffa L) Leaf Spot Caused by Coniella musaiensis Var Hibisci - K. D. Apeyuan; A. O. Nwankiti; O. A. H. Oluma; E. J. Ekefan (Contemporary Research and Perspectives in Biological Science Vol. 9, 2025)
The present study determining the effect of changes in sowing dates on disease severity of Roselle (Hibiscus sabdariffa L) leaf spot caused by Coniella musaiensis Var hibisci. Planting of Roselle around Makurdi, Central Nigeria is usually done at the onset of rains with no regards to pests and disease situation. However, several diseases affecting the plant have been identified and shown to limit the production of roselle worldwide. Five dates were selected with an interval of fourteen days (14) between the dates for two years (2003 and 2004) to determine the most appropriate time to sow the crop using two Roselle accessions; green (Acc1) and red (Acc3). The first date was determined by the establishment of the rains in the season. It was observed that change in sowing dates had significant (p = 0.05) effect on disease severity but not on plant height, number of branches, number of fruits and calyx yield. There is indication that severity in this disease has little effect on performance of other agronomic characters particularly when the plant survives the attack. The result however points to the fact that delayed planting of this crop would be ideal and as such Mid-July date becomes ideal for planting of roselle. Roselle is photosensitive, at whatever date the crop is planted, it will flower in August and be due for harvest in December. Hence, roselle should be cultivated mid-July to avoid the risk of heavy attack during heavy rains.